Psyche of Asian Society - Shukla, Anuradha, Ed. (New Delhi Cocept Publishing Company, 2019)
Every culture has its own values and, of course, they are different in every walk of life with more or less magnitude. We can see a lot of variation in two cultures in regard to their way of thought, way of behaviour parameters and so many other things. Asia is a big continent and it covers fourty eight countries in its roof. These countries are somehow similar in traditions and behaviour performance and vice versa in some other respects of life. But it is quite sure that there is a common thread that links them in one single garland. The aim of this volume is to collect the gems from entire Asia and bring them on one platform. There are twenty four articles in this volume. They reveal various aspects of the particular country where the work is done. Chapters are in theoretical and /or in empirical mode and we hope that they will provide good insight to the readers to move on their interest and research.
Keywords: Dube, Anubhuti, ed; Thagunna, Narendra Singh, ed; Asians-Psychology; Ethnopsychology-Asia; mentally ill-Asia; Psychology